Understanding the role of apolipoproteinA-I in atherosclerosis : Posttranslational modifications synergize dysfunction? - Díaz Ludovico, Ivo (2021)
Background: The identification of dysfunctional human apolipoprotein A-I (apoA-I) in atherosclerotic plaques suggests that protein structure and function may be hampered under a chronic pro inflammatory scenario. Moreover, the fact that natural mutants of this protein elicit severe cardiovascular diseases (CVD) strongly indicates that the native folding could shift due to the mutation, yielding a structure more prone to misfold or misfunction. To understand the events that determine the failure of apoA-I structural flexibility to fulfill its protective role, we took advantage of the study of a natural variant with a deletion of the residue lysine 107 (K107del) associated with atherosclerosis. Methods: Biophysical approaches, such as electrophoresis, fluorescence and spectroscopy were used to characterize proteins structure and function, either in native conformation or under oxidation or intramolecular crosslinking. Results: K107del structure was more flexible than the protein with the native sequence (Wt) but interactions with artificial membranes were preserved. Instead, structural restrictions by intramolecular crosslinking impaired the Wt and K107del lipid solubilization function. In addition, controlled oxidation decreased the yield of the native dimer conformation for both variants. Conclusions: We conclude that even though mutations may alter protein structure and spatial arrangement, the highly flexible conformation compensates the mild shift from the native folding. Instead, post translational apoAI modifications (probably chronic and progressive) are required to raise a protein conformation with significant loss of function and increased aggregation tendency. General significance: The results learnt from this variant strength a close association between amyloidosis and atherosclerosis.